(4-Fluorophenyl)(1H-pyrrol-2-yl)methanone - V. Prakash; Kamini Kapoor; M. Shet Prakash; Vivek K. Gupta; Rajni Kant (Acta Crystallographica Section E, 2012)
In the title molecule, C11H8FNO, the dihedral angle between the pyrrole and benzene rings is 49.16 (6)°. In the crystal, adjacent molecules are linked by pairs of N—H...O hydrogen bonds, forming inversion dimers.